2017
DOI: 10.4172/2165-7920.10001033
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab as First-Line Therapy in Severe Lupus Erythematosus with Neuropsychiatric and Renal Involvement: A Case-Report and Review of the Literature

Abstract: Neuropsychiatric and renal involvement are common in systemic lupus erythematosus with negative impact on patient survival. Glucocorticoids, antiproliferative and cytotoxic agents represent first-line therapies, but are often ineffective and are burdened by significant toxicities. Despite the negative results of two randomized controlled trials, rituximab is still widely used as second- or third-line therapy in similar cases. No case has been reported so far where rituximab has been used as first-line therapy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
2
0
2
Order By: Relevance
“…For patients with a confirmed diagnosis of NPSLE, current treatment options include glucocorticoids (GCs), immunosuppressants, biologics, intravenous immunoglobulins (IVIg), plasma exchange, and anticoagulant therapy 30–33 . Among the 20 cases reported in our study, only 12 reported treatment regimens.…”
Section: Discussionmentioning
confidence: 94%
“…For patients with a confirmed diagnosis of NPSLE, current treatment options include glucocorticoids (GCs), immunosuppressants, biologics, intravenous immunoglobulins (IVIg), plasma exchange, and anticoagulant therapy 30–33 . Among the 20 cases reported in our study, only 12 reported treatment regimens.…”
Section: Discussionmentioning
confidence: 94%
“…Die Wirksamkeit der RTX-Behandlung wurde auch bei refraktären Fällen mit neuropsychiatrischer Beteiligung, bei Patienten mit Delirium oder Psychose [52‒54] und bei ophthalmologischen Ausprägungen [55] berichtet. Darüber hinaus deuten einige Fallberichte darauf hin, dass RTX als Erstlinientherapie bei schwerem neuropsychiatrischem SLE [56], einschließlich des demyelinisierenden Syndroms als Folge von SLE, schwerer kognitiver Dysfunktion, Hirnstammerkrankung, Hirnnervenlähmungen und Schwäche und Taubheit in den Gliedmaßen [57], oder bei gleichzeitiger neuropsychiatrischer und renaler Beteiligung [58] nützlich sein kann.…”
Section: Empfehlungenunclassified
“…The effectiveness of RTX treatment was also reported in refractory cases with neuropsychiatric involvement, in patients with delirium or psychosis ( 52 54 ), and in the presence of ophthalmologic manifestations ( 55 ). Furthermore, some case reports suggest that RTX may be useful as 1 st line therapy in severe neuropsychiatric SLE ( 56 ), including demyelinating syndrome secondary to SLE, severe cognitive dysfunction, brainstem disease, cranial nerve palsies, and weakness and numbness in limbs ( 57 ) or with concurrent neuropsychiatric and renal involvement ( 58 ).…”
Section: Recommendationsmentioning
confidence: 99%